2012
DOI: 10.4161/derm.20434
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and asthma

Abstract: Asthma, one of the most prevalent diseases affecting people worldwide, is a chronic respiratory disease characterized by heightened airway inflammation, airway hyperresponsiveness and airflow obstruction in response to specific triggers. While the specific mechanisms responsible for asthma are not well understood, changing environmental factors associated with urban lifestyles may underlie the increased prevalence of the disorder. Vitamin D is of particular interest in asthma since vitamin D concentrations dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 90 publications
1
43
0
3
Order By: Relevance
“…Vitamin-D is a fat-soluble nutrient and steroid hormone that has classical actions like increasing calcium absorption and maintenance of bone health. Recently, cardiovascular diseases, inflammation, infectious diseases, multiple sclerosis, impaired physical functioning, allergic diseases and all-cause mortality have been related inversely to serum Vitamin-D concentrations [4,16]. The existence of associations of vitamin-D with asthma remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitamin-D is a fat-soluble nutrient and steroid hormone that has classical actions like increasing calcium absorption and maintenance of bone health. Recently, cardiovascular diseases, inflammation, infectious diseases, multiple sclerosis, impaired physical functioning, allergic diseases and all-cause mortality have been related inversely to serum Vitamin-D concentrations [4,16]. The existence of associations of vitamin-D with asthma remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…It is also believed to be a potent immune system regulator having a potential role in various allergic diseases [4]. A potential role of Vitamin-D in tuberculosis, pneumonia, inflenza and respiratory infections has been proposed [4]. The existence of associations of vitamin-D with asthma and allergy remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few intervention studies, evaluating vitamin D supplementation with asthma exists in the literature (155,156,162). One of them demonstrated that 1,200 IU per day in children was associated to 83% reduction in the risk of disease exacerbation.…”
Section: G) Vitamin D and Respiratory Diseasesmentioning
confidence: 99%
“…4 Según los datos de la Encuesta Nacional de Examen de Salud y Nutrición (National Health and Nutrition Examination Survey, NHANES), solamente un cuarto de los adolescentes y adultos de los Estados Unidos tienen una concentración adecuada de vitamina D. 5 Además de los efectos sobre el metabolismo del calcio y el desarrollo óseo, se cree que la vitamina D también regula intensamente el sistema inmunitario y tiene una función potencial en varias enfermedades alérgicas. 6 El hecho de que haya receptores de vitamina D (RVD) en todas las células (cerebro, corazón, estómago, páncreas, pezones, gónadas, linfocitos T y B, monocitos, pulmones, etc.) excepto en los huesos indica que la vitamina D participa …”
Section: Introductionunclassified